Silica nanoparticles aid in structural leaf coloration in the Malaysian tropical rainforest understorey herb Mapania caudata - Strout, Greg (Oxford University Press, 2013)
BACKGROUND AND AIMS: Blue-green iridescence in the tropical rainforest understorey sedge Mapania caudata creates structural coloration in its leaves through a novel photonic mechanism. Known structures in plants producing iridescent blues consist of altered cellulose layering within cell walls and in special bodies, and thylakoid membranes in specialized plastids. This study was undertaken in order to determine the origin of leaf iridescence in this plant with particular attention to nano-scale components contributing to this coloration. METHODS: Adaxial walls of leaf epidermal cells were characterized using high-pressure-frozen freeze-substituted specimens, which retain their native dimensions during observations using transmission and scanning microscopy, accompanied by energy-dispersive X-ray spectroscopy to identify the role of biogenic silica in wall-based iridescence. Biogenic silica was experimentally removed using aqueous Na(2)CO(3) and optical properties were compared using spectral reflectance. KEY RESULTS AND CONCLUSIONS: Blue iridescence is produced in the adaxial epidermal cell wall, which contains helicoid lamellae. The blue iridescence from cell surfaces is left-circularly polarized. The position of the silica granules is entrained by the helicoid microfibrillar layers, and granules accumulate at a uniform position within the helicoids, contributing to the structure that produces the blue iridescence, as part of the unit cell responsible for 2 ° Bragg scatter. Removal of silica from the walls eliminated the blue colour. Addition of silica nanoparticles on existing cellulosic lamellae is a novel mechanism for adding structural colour in organisms.